Study on thermal comfort by using an atmospheric pressure dependent predicted mean vote index - Ruivo, Celestino (2021)
The thermal environment index Predicted Mean Vote is a descriptor largely applied to evaluate the comfort sensation of people in moderate environments. Software tools based on the Fanger's method have been created and used, which application is limited for the sea level atmospheric pressure. A procedure for estimating the index of thermal comfort of individuals in environments at air pressure different from barometric pressure 0 m of altitude was recently introduced. In present study, indoor air state associated with neutral thermal comfort conditions of individuals in seating activity are predicted for atmospheric pressure values in the range between 65.0 kPa and 101.3 kPa. It was observed that neutral temperature diminishes with the decrease of barometric pressure. Dependencies of index PMV on the activity level, the clothing insulation, relative, air velocity and on relative humidity for two atmospheric pressure values are investigated. It is concluded that the impact of pressure of the environment on the index of thermal comfort must be also considered when sizing an air-conditioning system.